Isokinetic thigh muscle ratios in youth football: Effect of age and dominance - Forbes, H.; Sutcliffe, S.; Lovell, A.; McNaughton, L. R.; Siegler, J. C. (International Journal of Sports Medicine, 2009)
This study aimed to analyse the effect of age on muscle peak torque (PT), and Hamstring (H): Quadricep (Q) ratio in elite youth footballers. To date, no study has considered age-group playing level and pubertal development in this population. One hundred and fifty-seven elite youth footballers in the age groups U12 to U18 volunteered to participate in this study, 133 of these were further grouped for pubertal development. Prior to testing subjects completed separate familiarisation, a three minute cycle ergometer warm up (resistance 50-60W), and two sub-maximal repetitions. Concentric and eccentric isokinetic PT measures for reps 2-4 of H and Q muscle action were taken at 60° s-1. From this, conventional and functional H: Q ratio was calculated along with dominant: non dominant ratio for the concentric Q and H, and eccentric H conditions. Significant main effects were observed for the age/pubertal development group and PT in all muscles and conditions (P<0.05). Of particular interest was a significant main effect for age and Functional H: Q (P<0.05), which suggested a move away from equality at U18. Our study provides normative data for coaches, trainers and clinicians working with youth footballers and may also have connotations for injury prevention and performance.